Adjunctive ultrasonography during carotid artery stenting to minimize iodine contrast use. Issue 5 (21st March 2012) - Nammuni, Isuru; Batt, Paul; Erlich, Jonathan; Varcoe, Ramon L.
<x xml:space="preserve">Abstract</x> Carotid artery stenting (CAS) in patients with chronic kidney disease carries a significant risk of contrast‐induced nephropathy. We report a case of CAS with adjunctive sonography to reduce the amount of contrast medium during angiography. A 71‐year‐old man presented with a symptomatic right carotid stenosis. He was selected for CAS due to significant medical comorbidity, which included severe renal impairment. A preoperative noncontrast CT was performed to assess anatomical suitability and to plan arch vessel cannulation. We undertook CAS with the use of intraoperative ultrasound. Sonography was used to monitor the manipulation of wires, catheters, and stents. Four milliliters of contrast was required to complete the procedure successfully with no deterioration in postoperative renal function. Adjunctive ultrasound is feasible to reduce contrast use in patients with severe renal impairment undergoing CAS. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 41:323–326, 2013